Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning 2019
DOI: 10.1007/978-3-030-20062-6_17
|View full text |Cite
|
Sign up to set email alerts
|

From Needs Analysis to Large-Scale Implementation: Using Collaborative Design to Support ICT Integration

Abstract: The new mathematics curriculum for senior high school in Ghana encourages teachers to make use of the calculator and the computer for problem solving and investigations of real life situations. The goal is to help students acquire the habit of analytical thinking and the capacity to apply knowledge in solving practical problems. As a result, the government and other institutions have invested huge sums of money in procurement of computers and establishment of computer labs in most senior high schools; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Strengths and challenges were found in which the commitment on the part of university management is high; however, a loophole is found to have been created in relation to policy, infrastructure, and the capacity of academic staff. The building of the capacities of the academic staff of UCC is critical, especially in the area of their competencies (Agyei, 2019). There is the need to prioritize all three aspects in relation to the institution, instruction, and investment in considering the implementation and the efficacy of e-learning at UCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strengths and challenges were found in which the commitment on the part of university management is high; however, a loophole is found to have been created in relation to policy, infrastructure, and the capacity of academic staff. The building of the capacities of the academic staff of UCC is critical, especially in the area of their competencies (Agyei, 2019). There is the need to prioritize all three aspects in relation to the institution, instruction, and investment in considering the implementation and the efficacy of e-learning at UCC.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the critical factors that impede the integration of technological means of pedagogy and implementation have been researched among others to be the availability of infrastructure, the preparedness on the part of leadership in supporting it to function well, and the pedagogical competencies expected of the academic staff (Chigona & Dagada, 2011). Notwithstanding, the provision of the support systems made available to assist in the minimization of these identified problems is considered as limited (Agyei, 2019;Antwi et al, 2018;Tondeur et al, 2017). It could be argued that whiles these support systems are within the reach of the academic staff of higher institutions of learning and seems to have gained root in the pedagogical strategies employed by the academic staff of the advanced world, their counterpart in African counties acceptance and implementation is still at its infantile stages (Bhuasiri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to Kilpatrick et al (2001), concept understanding is the ability to understand concepts, operations, and mathematics relations. Cultivating the idea of learning stages emphasizes the delivery of new concepts to students (Agyei, 2019;Reis, 2010).…”
Section: Readmentioning
confidence: 99%
“…In contrast to many traditional approaches, where learners are passive participants, PBL makes students active, requires them to think, and often collaborate. Project-based learning has been shown to have a positive effect on creative thinking, communication and teamwork [39][40], and self-confidence. For example, Khairunnisa [41] showed that using project-based learning, with children, positively affected collabora-tion and teamwork, increased their self-confidence, creative thinking, willingness to take risks and express new ideas.…”
Section: Introductionmentioning
confidence: 99%